Hospital preparedness for COVID-19 pandemic: experience from department of medicine at Veterans Affairs Connecticut Healthcare System. Issue 6 (17th August 2020) - Gupta, Shaili; Federman, Daniel G.
ABSTRACT: The 2019–2020 pandemic Coronavirus Disease 2019 (COVID-19) has inundated hospital systems globally, as they prepare to accommodate surge of patients requiring advanced levels of care. Pandemic preparedness has not been this urgently and widely needed in the last several decades. According to epidemiologic predictions, the peak of this pandemic has still not been reached, and hospitals everywhere need to ensure readiness to care for more patients than they usually do, and safety for healthcare workers who strive to save lives. We share our hospital-wide rapid preparedness and response to COVID-19 to help provide information to other healthcare systems globally.